Crystalline and Polymeric Interactions in Multi- layered Bulletproof Glass: A Study of Ballistic Resistance and Structural Integrity - Mohd. Yelwa Jibrin (International Journal of Crystalline Materials, 2024)
Bulletproof glass is engineered to withstand high-impact projectiles, offering a critical line of defense in various industries such as banking, military, and armored vehicles. This study explores the structural composition, energy absorption mechanisms, and performance characteristics of bulletproof glass when exposed to ballistic threats. The glass consists of layered constructions, often involving polycarbonate and adhesive interfaces such as polyvinyl butyral, which enhance its energy absorption and resistance to projectiles. The performance of bulletproof glass typically degrades after multiple impacts, with thin sheets requiring 3-5 shots from a mid-power handgun (9 mm) to be penetrated. Laminated bulletproof glass operates by distributing the energy of a projectile across multiple layers, which helps absorb shock waves and prevent bullet penetration. The design also incorporates flexible materials to absorb energy and reduce the chance of complete perforation. Glass thickness ranges from 19 to 89 mm, depending on the application, offering varying levels of protection. Over time, bulletproof glass exposed to UV radiation may discolor, but this does not affect its protective capabilities. Advancements in materials, such as Soda-Lime Silicate (SLS) glass strengthened through ion exchange, have improved the strength and durability of bulletproof windows, while maintaining their transparency and reducing overall thickness. Adhesive durability in lamination, as well as innovations in lightweight materials like Kevlar composites, also contribute to enhancing ballistic performance. This study underscores the importance of material selection, layer configuration, and adhesive properties in optimizing the safety and effectiveness of bulletproof glass systems, making it an essential component in high-security environments.
Keywords: Bulletproof glass; ballistic protection; kevlar composites; laminated glass; polycarbonate layers